Changes in soil organic carbon fractions in response to wheat straw incorporation in a subtropical paddy field in China. Issue 2 (30th December 2020) - Dai, Wei; Gao, Hui; Sha, Zhimin; Penttinen, Petri; Fang, Kaikai; Wang, Jun; Cao, Linkui
Abstract: Background : Optimal wheat straw management in paddy fields is important for evaluating soil organic carbon (SOC) dynamics and sustaining soil quality. Aims : We investigated the effects of wheat straw incorporation in paddy soil on the total SOC content, soil labile organic C fractions [water soluble organic C (WSOC), hot‐water soluble organic C (HWSOC), easily oxidizable C (EOC), microbial biomass C (MBC), particulate organic C (POC), and light fraction organic C (LFOC)], and C pool management index (CPMI). Methods : Rice (var. Qingjiao 307) was grown from June to November 2019 in a subtropical paddy field, under four different treatments: without any amendments (control; CK); with N, P, and K fertilizers (NPK); with NPK and a moderate rate of wheat straw application (NPKS1); and with NPK and a high rate of wheat straw application (NPKS2). Soil samples were collected from depths of 0–5, 5–10, 10–20, and 20–30 cm after the rice was harvested. Results : In all soil layers, the bulk density was 10.79–51.85% lower and the total SOC, WSOC, HWSOC, EOC, MBC, POC, and LFOC contents were 13.87–145.97% higher in the NPKS2 treatment than in the CK treatment ( p < 0.05). The CPMI was highest in the NPKS2 treatment in the top 20 cm soil. SOC correlated positively with labile C fractions and CPMI in the 0–5 and 5–10 cm soil layers ( p < 0.05), with the exception of WSOC and LFOC in the 5–10 cm soil layer. The sensitivity of each soil labile organic C fraction to the different treatments varied in the 0–5 cm soil layer. Rice yield was highest in the NPKS2 treatment. Conclusions : Overall, the NPKS2 treatment had a positive effect on SOC stocks and higher soil quality in subtropical paddy soils in China.